How would I solve this equation in the Factor Completely form?

How would I solve this equation in the Factor Completely form?

12t^3+24t^2-4t-8

### 1 Answer | Add Yours

`12t^3+24t^2-4t-8 = 0`

you can take 12t^2 and 4 out of the first two terms and last two terms like this

`12t^2(t+2)-4(t+2) = 0`

taking 4(t+2) out from whole,

`4(t+2)(3t^2-1) = 0`

this gives you,

`4(t+2)(sqrt(3)t-1)(sqrt(3)t+1) = 0`

the solutions are,

`t+2 = 0 , t = -2`

`sqrt(3)t-1 = 0, t= 1/sqrt(3)`

`sqrt(3)t+1 = 0, t= (-1)/sqrt(3)`

the solutions are, `-2, 1/sqrt(3) and (-1)/sqrt(3)`

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes